Fitspiration on social media: Body-image and other psychopathological risks among young adults. A narrative review. (2021) - Cataldo, Ilaria; De Luca, Ilaria; Giorgetti, Valentina; Cicconcelli, Dorotea; Bersani, Francesco Saverio; Imperatori, Claudio; Abdi, Samira; Negri, Attilio; Esposito, Gianluca; Corazza, Ornella
Abstract: Background: The use of social media is popular in the health and the beauty industry, with an increasing number of brands using web platforms to promote their products. Among the recently-emerged trends, "fitspiration" (also abbreviated as "fitspo") has raised health concerns. Evidence suggested that fitspiration contents, although originally conceived to promote a healthier lifestyle, often portray distressful themes that can lead to unhealthy thoughts and behaviours (e.g., body image and eating disturbances, excessive exercising, misuse of supplements). Despite its popularity, the knowledge on this trend is limited and relatively few studies explored its psychological impact on young people below 25-year-old. Methods: A narrative literature search was conducted in order to provide an overview of the evidence linking fitspiration trends on social media to mental health disturbances. Results: Various factors related to psychopathological risks have been associated with the exposure to fitspiration contents, which we have clustered in the following main topics: (i) exercise addiction and compulsive exercise; (ii) body dissatisfaction and objectification; (iii) appearance-related anxiety and depressive symptoms, self-esteem; (iv) excessive control of eating habits; (v) use of enhancing drugs; (vi) quality of life. Conclusion: A wide range of negative psychological effects associated with fitspiration contents on social media were identified. Additional research is required to further elucidate the phenomenon, to determine the extent of the harm for young people, and to develop preventive mental health strategies.